Alasan Amerika Serikat Mundur Dari Intermediate-Range Nuclear Forces Treaty (INF Treaty) Tahun 2019 - Jannah, Miftachul; Aisyah, Aisyah; Yuniarti, Yuniarti (Department of International Relations, Universitas Mulawarman, 2023)
On August 2, 2019, the United States officially withdrew from the INF Treaty. The United States' decision was announced in a press release by the Ministry of Foreign Affairs. This study aims to explain the reasons for the withdrawal of the United States. As an analytical tool, this study uses the Decision Making Process Theory by William D. Coplin where the results of the research shows that US decisions are influenced by internal and external factors. Internal factors include Donald Trump's America First Policy, and the domination of the Republican Party in the Congress which has led to an increase of United States military budget while external factors are based on Russia's offence of 9M729 missile possess and threats of China's military capability enhancement which is not parties to the INF Treaty.